Ecology and ecosystems of the Borana deep wells area - Bille, Jean-Claude; Eshete, A.; Corra, M. (International Livestock Centre for Africa, 1983)
Describes the vegetation & major landscape features of the Dass, Web-Arero, Melbana & Goff-Ley well areas in Borana, Sidamo, southern Ethiopia, all of which represent a historical sequence in the overgrazing of rangelands. Includes a literature review of bush control, and a list of interventions to eliminate/better utilise the effects of bush encroachment in the Sidamo area.